Age-associated distribution of normal B-cell and plasma cell subsets in peripheral blood - Blanco, Elena; Pérez-Andrés, Martín; Arriba-Méndez, Sonia; Contreras-Sanfeliciano, Teresa; Criado, Ignacio; Pelak, Ondrej; Serra-Caetano, Ana; Romero, Alfonso; Puig, Noemí; Remesal, Ana; Torres Canizales, Juan; López-Granados, Eduardo; et al. (The Journal of allergy and clinical immunology, 2018)
BACKGROUND: Humoral immunocompetence develops stepwise throughout life and contributes to individual susceptibility to infection, immunodeficiency, autoimmunity, and neoplasia. Immunoglobulin heavy chain (IgH) isotype serum levels can partly explain such age-related differences, but their relationship with the IgH isotype distribution within memory B-cell (MBC) and plasma cell (PCs) compartments remains to be investigated. OBJECTIVE: We studied the age-related distribution of MBCs and PCs expressing different IgH isotypes in addition to the immature/transitional and naive B-cell compartments. METHODS: B-cell and PC subsets and plasma IgH isotype levels were studied in cord blood (n = 19) and peripheral blood (n = 215) from healthy donors aged 0 to 90 years by using flow cytometry and nephelometry, respectively. RESULTS: IgH-switched MBCs expressing IgG1, IgG2, IgG3, IgA1, and IgA2 were already detected in cord blood and newborns at very low counts, whereas CD27+IgM++IgD+ MBCs only became detectable at 1 to 5 months and remained stable until 2 to 4 years, and IgD MBCs peaked at 2 to 4 years, with both populations decreasing thereafter. MBCs expressing IgH isotypes of the second immunoglobulin heavy chain constant region (IGHC) gene block (IgG1, IgG3, and IgA1) peaked later during childhood (2-4 years), whereas MBCs expressing third IGHC gene block immunoglobulin isotypes (IgG2, IgG4, and IgA2) reached maximum values during adulthood. PCs were already detected in newborns, increasing in number until 6 to 11 months for IgM, IgG1, IgG2, IgG3, IgA1, and IgA2; until 2 to 4 years for IgD; and until 5 to 9 years for IgG4 and decreasing thereafter. For most IgH isotypes (except IgD and IgG4), maximum plasma levels were reached after PC and MBC counts peaked. CONCLUSIONS: PC counts reach maximum values early in life, followed by MBC counts and plasma IgH isotypes. Importantly, IgH isotypes from different IGHC gene blocks show different patterns, probably reflecting consecutive cycles of IgH isotype switch recombination through life.
Keywords: Young Adult; flow cytometry; subclass; imunologická paměť; imunoglobulinové izotypy; Male; Aging; Child, Preschool; Immunologic Memory; normal B cells; mladý dospělý; Adolescent; Infant; Child; Plasma Cells; reference ranges; B-lymfocyty; dítě; Adult; Immunoglobulin Class Switching; Immunoglobulin Heavy Chains; Aged; dospělí; memory B cells; mužské pohlaví; senioři; plasma cells; mladiství; novorozenec; předškolní dítě; senioři nad 80 let; lidé; ženské pohlaví; humorální imunita; Humans; Infant, Newborn; kojenec; stárnutí; Aged, 80 and over; IgH isotype; těžké řetězce imunoglobulinů; B-Lymphocytes; plazmatické buňky; age-related values; Female; Immunity, Humoral; přesmyk imunoglobulinových tříd; Immunoglobulins; lidé středního věku; Immunoglobulin Isotypes; Middle Aged